UPAYA KEPOLISIAN DALAM MENERTIBKAN PELANGGARAN LALU LINTAS KHUSUSNYA BALAP LIAR DIWILAYAH HUKUM POLRES KUTAI TIMUR - Magdalena, Lidya (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACT       Illegal racing is an arena for speeding vehicles, especially motorized vehicles, where motor racing is carried out without official permission and is held on the highway including public facilities. Usually this wild race activity is carried out in the middle of the night until early morning when the atmosphere of the highway has begun to lane, Actors of illegal racing do not care if there are other motorists on the public road, their main goal is to win a wild race that was held at that time. They even ignore the safety of others and their own safety.Traffic Police Efforts in controlling illegal motorbike action can be seen from the results of the translation as well as from the activities carried out by the traffic police in efforts to prevent illegal motorbike racing actions.The need to add activities in the process of control through coaching to overcome and prevent, this is done so as not to cause unrest for the community in order to create a sense of security and give guidance about the dangers of illegal motor racing action to the perpetrators and the public. Keywords: Police Efforts, Wild Race